2005
DOI: 10.1042/bj20050196
|View full text |Cite
|
Sign up to set email alerts
|

MSKs are required for the transcription of the nuclear orphan receptors Nur77, Nurr1 and Nor1 downstream of MAPK signalling

Abstract: MSK (mitogen- and stress-activated protein kinase) 1 and MSK2 are kinases activated downstream of either the ERK (extracellular-signal-regulated kinase) 1/2 or p38 MAPK (mitogen-activated protein kinase) pathways in vivo and are required for the phosphorylation of CREB (cAMP response element-binding protein) and histone H3. Here we show that the MSKs are involved in regulating the transcription of the immediate early gene Nur77. Stimulation of mouse embryonic fibroblasts with PMA, EGF (epidermal growth factor)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
102
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 72 publications
7
102
1
1
Order By: Relevance
“…In addition to a MEF2 site, the nur77 promoter is also regulated by SRE and AP-1/CRE-like sequences. In most cell types the MAPK-dependent transcription of nur77 requires the phosphorylation of CREB by MSKs [35]. However, in T cells TCR-induced nur77 transcription, while dependent on MAPK signalling, is independent of MSKs and CREB phosphorylation [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to a MEF2 site, the nur77 promoter is also regulated by SRE and AP-1/CRE-like sequences. In most cell types the MAPK-dependent transcription of nur77 requires the phosphorylation of CREB by MSKs [35]. However, in T cells TCR-induced nur77 transcription, while dependent on MAPK signalling, is independent of MSKs and CREB phosphorylation [49].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was reverse-transcribed using iScript (BioRad), and real-time PCR carried out using Sybrgreen based detection methods (BioRad). Primers for 18s, nur77, nor1 and egr3 have been described previously [35,49]. Primer sequences for ERK5, IL-2, IL-4, IL-13, IFN-g and IkBa are listed in Table 3.…”
Section: Quantitative Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Nr4a1 (also known as nur77 and NGFI-B) belongs to a subfamily of orphan nuclear receptors, whose other members are Nr4a2 [also known as Rnr-1 (ribonucleotide reductase-1), Not, and Nurr1] and Nr4a3 [also known as Nor-1 (neuron-derived orphan receptor-1) and Tec], all of which function as transcription factors (Ryseck et al, 1989;Steinmetz et al, 2001). Several studies have implicated Nr4a1 and Nr4a2 as CREB target genes (Fass et al, 2003;Darragh et al, 2005;von Hertzen and Giese, 2005ab). Also, Fass et al (2003) observed that forskolin-induced Nr4a1 expression was increased by TSA treatment, whereas Nr4a3 expression was not enhanced by TSA (Fass et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…MSKs are able to regulate transcription by the phosphorylation of both transcription factors, including CREB (cAMP-response-element-binding protein) and ATF1 (activating transcription factor) [1][2][3][4][5][6], and the chromatinassociated proteins HMG-14 (high-mobility group 14) and histone H3 [7][8][9][10]. Genes reported to be regulated by MSK downstream of CREB or ATF1 include c-fos [11], junB [4], MUC5A (mucin 5A) [12] and genes encoding the NR4A group of nuclear orphan receptors [13].…”
Section: Introductionmentioning
confidence: 99%